Analysis of taboos as a basic principle of religious beliefs in the context of modern religious studies - Serhiy Titov (Cхід, 2018)
The article analyzes some definitions of a taboo, which are well-known in modern religious studies, and looks into a taboo generation mechanism (by the example of G. R. Stephenson's experiment with rhesus monkeys). The author considers that originally a taboo is a religious phenomenon and, proceeding from the above, systematizes the areas falling under its influence. Special attention is given to a number of prohibitions related to the sacred area. It is indicated that all the spheres of life in primitive societies are regulated by sacred taboos which replace law, ethics and religion. In civilized societies taboos are represented by verbalized forms of the sacred. The author asserts that any kind of a prohibition is of absolutely religious nature by its origin and draws a conclusion that the phenomenon of taboo is a particular case of a religious prohibition both in primitive societies and modern religious traditions. The novelty of the given research is an attempt to look for ontological grounds for taboo generation in terms of religious studies.